Mekanisme Transaksi E-Commerce (Jual Beli Online) Menurut Perspektif Ekonomi Syariah Studi Kasus Masyarakat Muslim Indonesia, Malaysia, dan Singapura - Ayu, Kemala; S, Syahfawi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The development of information technology has brought about a major transformation in global trade practices through the mechanism of e-commerce. This phenomenon also affects Muslim communities in Southeast Asia, particularly in Indonesia, Malaysia, and Singapore. The increasingly popular online buying and selling transactions raise important questions regarding their compatibility with Sharia economic principles such as the prohibition of usury, gharar, and maysir, as well as the need for honesty and transparency. This study aims to analyze how e-commerce transaction mechanisms are applied by the Muslim community in the third country and the extent to which compliance with Shariah principles is applied. The results of the study show that although progress has been made in integrating Shariah values into digital transactions, there are still significant challenges, including low digital Shariah literacy, lack of comprehensive regulation, and supply chain complexity. The study concludes that collaboration between governments, business actors, and religious authorities is essential to build a sustainable and fair Shariah e-commerce ecosystem.